2016
DOI: 10.1002/2015ef000321
|View full text |Cite
|
Sign up to set email alerts
|

The need for accurate long‐term measurements of water vapor in the upper troposphere and lower stratosphere with global coverage

Abstract: Water vapor is the most important greenhouse gas in the atmosphere although changes in carbon dioxide constitute the “control knob” for surface temperatures. While the latter fact is well recognized, resulting in extensive space-borne and ground-based measurement programs for carbon dioxide as detailed in the studies by Keeling et al. (1996), Kuze et al. (2009), and Liu et al. (2014), the need for an accurate characterization of the long-term changes in upper tropospheric and lower stratospheric (UTLS) water v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Given the water vapor offsets between the satellite instruments demonstrated here, the potential data gap in the water vapor record would severely impact our confidence in characterizing decadal variability and trends in water vapor. As discussed by Müller et al (2016) and demonstrated in this paper, it is possible that a global network of balloon-borne hygrometer measurements could help serve as a transfer standard between satellites and minimize the impact of a potential water vapor data gap in the satellite record.…”
Section: Discussionmentioning
confidence: 99%
“…Given the water vapor offsets between the satellite instruments demonstrated here, the potential data gap in the water vapor record would severely impact our confidence in characterizing decadal variability and trends in water vapor. As discussed by Müller et al (2016) and demonstrated in this paper, it is possible that a global network of balloon-borne hygrometer measurements could help serve as a transfer standard between satellites and minimize the impact of a potential water vapor data gap in the satellite record.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach determines the calibration factor using simultaneous measurements from a collocated reference instrument. Approaches on this second technique include water vapor comparisons with radiosondes, satellites and microwave radiometers (Ferrare et al, 1995;Mattis et al, 2002;Miloshevich et al, 2004;Madonna et al, 2011;Leblanc et al, 2012;Reichardt et al, 2012;Navas-Guzmán et al, 2014;Foth et al, 2015). The accuracy of the calibration factor derived using these techniques fluctuates between 5 and 10 %.…”
Section: Lidar Water Vapor Calibration Methodsmentioning
confidence: 99%
“…Furthermore, the wind-driven drifting of the device can be misleading in terms of geographical location of the vertical information. In contrast, remote sensing techniques such as microwave radiometers (England et al, 1992;Reagan et al, 1995), differential absorption lidars (DIALs) (Bösenberg, 1998), photometers (Barreto et al, 2013) and Raman lidars Ferrare et al, 1995;Turner et al, 2002;Whiteman, 2003;Leblanc et al, 2012;Navas-Guzmán et al, 2014;Foth et al, 2015) have been successfully adopted in water vapor studies. While microwave radiometers and photometers can accurately deliver the total precipitable water vapor (TPW), lidars (DIAL and Raman) are the only instruments available for high temporal and vertical resolution of continuous WVMR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…They are also well suited to investigate long-term changes in the stratosphere. In particular, for the investigation of long-term changes, high precision and accuracy are needed in combination with rather low costs (Müller et al, 2016;Moore et al, 2014). Most in situ measurements in the stratosphere require the use of large and expensive balloons to carry instruments above altitudes of 20 km.…”
Section: Discussionmentioning
confidence: 99%
“…An extension of the AirCore technique to other tracers gases as suggested by may provide a valuable addition as these gases can also be used to study long-term changes in the stratosphere. Müller et al (2016) suggested that a long-term network for water vapour measurements in the stratosphere should be set up to monitor this radiatively important trace gas. We suggest that such a network could be complemented by AirCore observations.…”
Section: Discussionmentioning
confidence: 99%